2017
DOI: 10.1007/s00467-017-3622-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of myocardial function in childhood chronic kidney disease, during dialysis, and following kidney transplantation

Abstract: There are differences in diastolic parameters in childhood CKD that persist during dialysis and after transplantation. Systolic parameters are preserved, with significant improvement in systolic myocardial deformation following transplantation. The impact of persistent diastolic changes on long-term outcomes requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
3
34
0
4
Order By: Relevance
“…However, the LVMI did not change in children without LVH before RTx. Although some investigators have reported controversial findings regarding the change in the LVMI associated with RTx in children, this study specifically evaluated the LVMI according to the presence of pre‐existing LVH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the LVMI did not change in children without LVH before RTx. Although some investigators have reported controversial findings regarding the change in the LVMI associated with RTx in children, this study specifically evaluated the LVMI according to the presence of pre‐existing LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, removal of volume overload and uremic toxins following RTx is likely to lead to the improvement of LVH. However, the effects of RTx on cardiac function in children with CKD remain controversial …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations